ZAMONAVIY TA’LIMNI TASHKIL ETISH VA O‘QUVCHILARDA KREATIV SIFATLARNI RIVOJLANTIRISH - Jumanov М.A.; Matrasulov, Ǵ.J.; Kurbanova, G.S. (SCIENCE and SOCIETY, 2023)
Subjects taught in general education schools play a special role in the development of creative abilities of students. After all, regardless of whether they are of a social, humanitarian, natural or practical nature, the tasks given to students in the classes organized by academic subjects make them think, think, think logically, the subject being studied encourages to put forward original ideas. This article covers the world educational experience of developing the creative abilities of students of general education schools, the researches being conducted in this regard, as well as the issues of effective organization of modern education and development of creative qualities in students.